Evaluation of chemokine receptors (CCRs) expression on peripheral blood T-lymphocyte subsets in patients with thoracic aortic aneurysm - Tiwari, Kaushal Kishore; Sbrana, Silverio; Bevilacqau, Stefano; Gasbari, Tommaso; Santarelli, Filippo; Solinas, Marco; Glauber, Mattia (Journal of College of Medical Sciences-Nepal, 2016)
Background & Objectives: Mortality and morbidity from the complication of aortic aneurysm remain very high. Aortic size index, which classify thoracic aortic aneurysm patients in three risk groups for aortic rupture prediction. Recent data support that aortic wall remodeling is a dynamic process with active involvement of the chronic inflammation and immunological system. Aim of our study is to evaluate expression level of chemokine receptors known to be involved in the T-cells migration and to correlate them with aortic size index. Materials & Methods: Total 20 patients undergoing surgery for ascending aortic aneurysm and/or aortic valve surgery were enrolled. Aortic size index was calculated. Preoperatively blood samples collected. By flowcytometry and dual parameter dot plot technology percentage of positivity of CCR5 on these T-cell subsets were quantified. Results: Mean age of the patients was 67±5.93 years. Majority of patients had hypertension. Mean ascending aortic diameter was 42.1±8.14 mm. Mean Aortic size Index was 22.21±3.38 mm/m2. A statistical significance has observed between aortic size index and the expression of CCR5 on total CD4 positive T-cells (p-0.0949), and between aortic size index and CCR5 expression on the total CD3 positive T-cells (p-0.0293). Significant correlation observed between ASI and CCR5 expression on the CD8+/CD3+ T-cell subset (p-0.0183). Similarly, strong positive relationship between ASI and the expression of CCR5 on the cytotoxic CD28-/CD4+ T-cell subset (p-0.0055). Activated state of cytotoxic CD28-/CD4+ cell also correlated with aortic size index (p-0.0668). Conclusion: We conclude that T-cell mediated cytotoxic mechanism driven by CCR5 play an important role in the pathophysiology of the thoracic aortic aneurysm. JCMS Nepal. 2016;12(1):23-27.